Professor Dr. Nasrullah Ghasemi Dehkordi (1952-2023): The Founder of Iranian Herbal Pharmacopoeia - Abdolali Mohagheghzadeh (Shiraz University of Medical Sciences, 2023)
During their service as a faculty member, each pharmacy professor is faced with various duties including: teaching in the field of expertise, interdisciplinary research, executive responsibilities, and activity in the field of pharmacy, industry, or hospital. The important issue is whether all these activities or a part of them can ultimately lead to the excellence of the professor by meeting at least one exceptional need of the society.The late Dr. Ghasemi Dehkordi (1952-2023), our previous professor at the Isfahan Faculty of Pharmacy, mainly focused on the standardization protocols of medicinal plants during his academic activity (up to 2016). He did management a group of pharmacognosists, botanists, pharmacologists and related disciplines responsible for the compilation of Iranian herbal Pharmacopoeia.Isfahan, which was once the historical origin of the transfer of part of pharmacopoeial knowledge to the West through the Latin translation of a Persian manuscript of Qarabadin Irani in 1681, Pharmacopea Persica, once again gained the centrality of compiling the Iranian pharmacopoeia. A valuable work that must continue, and for that mentees are needed with the same dedication as the late mentor Dr. Ghasemi Dehkordi